COL7A1 indicates crucial potential as a basal membrane-related prognostic biomarker and therapeutic target in lung adenocarcinoma - Zhang, Jiao; Zi, Rui; Hu, Ping; Jiang, Zongying; Lv, Ye; Zhang, Haixia; Zhao, Yanjiao; Wang, Yan; Zhao, Lujun (Frontiers in Pharmacology, 2025)
IntroductionLung adenocarcinoma (LUAD) is the most prevalent subtype of lung cancer. Basal membrane (BM) is important to the invasive processes of LUAD. Our object is to explore hub BM-related genes in LUAD.MethodsThe gene expression data of LUAD were downloaded from The Cancer Genome Atlas and Gene Expression Omnibus databases. The weighted gene co-expression network analysis and differentially expressed gene analysis were used to identify candidates. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were used to evaluate their functions. Univariate Cox regression analysis was used to evaluate the prognostic value, and multivariate Cox regression analysis was used to verify its independence as a prognostic risk factor. The qPCR and Western blot were performed to ascertain the hub gene expression. The survival curve of two groups was drawn using Kaplan-Meier method. The hub gene-related immune characteristics were analyzed in independent cohorts by ESTIMATE and CIBERSORT methods.ResultsWe successfully identified COL7A1 as a BM-related prognostic biomarker in LUAD, with elevated expression compared to controls, and associated with poor prognosis. Functional enrichment analysis revealed it was involved in pathways related to cell proliferation and inflammation like ECM-receptor interaction. Time-dependent ROC analysis results showed that the AUC of COL7A1 in predicting 1-, 3-, and 5-year survival all exceeded 0.78. Immune infiltration characteristic analysis showed that the higher COL7A1 expression group exhibited lower ESTIMATE scores and higher TIDE scores.DiscussionOur study identified COL7A1 as a reliable BM-related prognostic biomarker, providing a new reference for the mechanistic understanding and target therapy of LUAD.